KEBERMAKNAAN HIDUP PADA HAFIDZUL QURâAN - Husnawati, Aula Sari; Nur Anganthi, Nisa Rachmah; partini, partini (Universitas Muhammadiyah Surakarta, 2006)
Every normal people basically wants to be useful and has value for himself, his family, and his society. They describe basic desire from human being, that is desire to have meaningful life. The meaningful life will give effects happiness, and if the desire can not be fulfilling, it will give effect like disappointed life and unmeaningful life, and if this condition always happens, it will make so many feelings and adaption that will hamper his self-development and the self-value. Praying is one of the methods that can be used to open someoneâs mind about the potential values and the meaningful life inside and outside. Khidmat and Khusyuâ praying actually can bring peace, stable and able to endure, and also it causes feeling as if he got guidance to do important things. So, he can live in religion way that will give him happiness and meaning. Hifdzul Qurâan (memorizing Al Qurâan) is one of the praying shape so it can open someoneâs mind about potential values and the meaningful life inside and outsideThe aims of this reasearch are to understand and describe clearly about the dimension of meaningful life for Hafidzul Qurâan. The informan of this research are 2 person who can memorize 30 juz of Al Qurâan, male and female, and have reminded for 1 year. The collecting data methods are interview and observation, and the data analysis used descriptive analysis. Based on the analysis, can be conclused that the comprehending of life meaningfully for the hafidzul qurâan always can be fulfilling by life experiences with development and actualization of the potention that someoneâs has., especially by hifdzul Qurâan activity, the life goal in the world or in the here-after, also the implementation of religion values and human values in the lifetime.Â